2016
DOI: 10.1002/eji.201646550
|View full text |Cite
|
Sign up to set email alerts
|

S1P1 downregulation tailors CD8+ T‐cell residence time in lymph nodes to the strength of the antigenic stimulation

Abstract: T cells are sequestered for several days in lymph nodes following antigen recognition but the precise mechanism regulating their timing of egress is not fully understood. In particular, whether interactions with antigen-presenting cells (APCs) and/or strength of the TCR stimulation shape T-cell residence time is unclear. We report here that the probability of T-cell egress decreases upon stimulation with high affinity TCR ligands. In contrast, low affinity peptides favor early egress, a phenomenon that could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(43 reference statements)
0
6
1
Order By: Relevance
“…Finally, we assume that immune checkpoint blockade is persistent and nearly complete, and the exhaustion rate of effector T cells is very small. [ 45 , 54 , 55 ] These assumptions simplified the analysis, allowing us to focus on the systemic transport limitations rather than biological impediments to T cell activation and killing. Where significant T cell exhaustion occurs, a continued antitumor immune response would require the activation of additional nT‐cell clones as previous effector T cells become ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we assume that immune checkpoint blockade is persistent and nearly complete, and the exhaustion rate of effector T cells is very small. [ 45 , 54 , 55 ] These assumptions simplified the analysis, allowing us to focus on the systemic transport limitations rather than biological impediments to T cell activation and killing. Where significant T cell exhaustion occurs, a continued antitumor immune response would require the activation of additional nT‐cell clones as previous effector T cells become ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…The residence time in each lymph node is 10 h, and the residence times for the other organs are listed in Table S1 (Supporting Information). [ 44 , 45 ] We assume that any nT‐cell that enters the blood system of a lymph node will extravasate into the node via HECs. Once in the node, we use a threshold to determine whether the nT‐cell becomes activated based on the local level of antigen in that node.…”
Section: Introductionmentioning
confidence: 99%
“…After a few hours of scanning antigen‐presenting cells in the T cell zone for the presence of cognate antigen, most T cells will exit the LN again by exiting via the efferent lymphatic vessel. By contrast, if a T cell encounters its cognate antigen on an antigen‐presenting cell, it will become activated, proliferate, and differentiate, to give rise to millions of antigen‐specific effector cells, which after several days will also leave the LN 50,55–57 . Both naïve and antigen‐specific lymphocytes exit the LN parenchyma through blind‐ended lymphatic cortical sinuses that emerge adjacent to HEVs in the paracortex.…”
Section: General Structure and Function Of The Lymphatic Systemmentioning
confidence: 99%
“…By contrast, if a T cell encounters its cognate antigen on an antigen‐presenting cell, it will become activated, proliferate, and differentiate, to give rise to millions of antigen‐specific effector cells, which after several days will also leave the LN. 50 , 55 , 56 , 57 Both naïve and antigen‐specific lymphocytes exit the LN parenchyma through blind‐ended lymphatic cortical sinuses that emerge adjacent to HEVs in the paracortex. The cortical sinuses merge into medullary sinuses, which further connect with the efferent lymphatic vessel leaving the LN.…”
Section: General Structure and Function Of The Lymphatic Systemmentioning
confidence: 99%
“…FTY720, also known as fingolimod, is a new generation immune suppressant that is extracted from the Traditional Chinese Medicine Cordyceps sinensis, with the major component ISP-I (also known as myriocin) having immune suppressing roles that induce lymphocyte apoptosis, accelerate matured lymphocyte nesting and inhibit translocation of T cells from the thymus to the peripheral blood circulation, and thus serving a role in transplantation immunity with strong effects and minor side effects (15). A recent study confirmed the role of FTY720 in regulating autoimmune diseases such as encephalomyelitis (16); however, the role of FTY720 in MG remained unknown. The aim of the present study was to investigate the role of FTY720 in MG and its underlying therapeutic mechanism, as well as providing a basis for the discovery of novel treatment approaches for MG.…”
Section: Introductionmentioning
confidence: 99%